Gene expression in the CNS of lactating rats with different patterns of maternal behavior. (October 2015) - de Moura, Ana Carolina; Lazzari, Virgínia Meneghini; Becker, Roberta Oriques; Gil, Mirela Severo; Ruthschilling, Carina Anicet; Agnes, Grasiela; Almeida, Silvana; da Veiga, Ana Beatriz Gorini; Lucion, Aldo Bolten; Giovenardi, Márcia
Highlights: Variations of maternal care are linked with differentiated gene expression in OB. The OB of HL mothers expressed more Drd1a, Prlr, Htr1a, Htr1b and Esr1 than LL. No difference of gene expression was found in the HP, PFC or ST of mothers LL or HL. There were differences of gene expression in the HP between lactating and virgins. LL showed a decrease in the frequency of nursing and remained longer off the pups. Abstract: For most mammalian species, maternal behavior has an essential role in the development of the offspring. The frequency of licking/grooming (LG) the pups has been used as a parameter to evaluate maternal care, having mothers with high (HL) or low (LL) frequencies of LG. This study aimed to analyze the gene expression of the receptors for dopamine (Drd1a), prolactin (Prlr), serotonin (Htr1a, Htr1b), estrogen (Esr1, Esr2), and of Bdnf in the olfactory bulb (OB), hippocampus (HP), prefrontal cortex (PFC), and striatum (ST) of Wistar rats from three groups: LL ( n  = 8); HL ( n  = 8); virgin females in diestrus (D; n  = 6). Maternal behavior was studied between the 1st and 7th postpartum days. Brain parts were analyzed by qRT-PCR. LL showed a decrease in the frequency of nursing, and an increase of remaining off the pups. There was an increase in gene expression of Drd1a, Prlr, Htr1a, Htr1b and Esr1 in the OB of HL, compared to LL. In the HP, Drd1a, Prlr and Htr1a were differently expressed when comparing HL, or LL, with D. The main finding is that HL had higher gene expression levels in the OB, which is a crucial structure to promote behavioral differences.